The Research Aims to Find Out The Effect Of Feeding Which is Given The Addition Boster Grotop With Different Doses in Feed Towards The Growth and Viability Of Seed Of Red Tilapic Fish (Oreochromis sp) Which Keep in Brackfish Water. - Rasyidah Utami; Niken Ayu Pamungkas; Mulyadi Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT             This research was done in during March - April 2018 in Technical Implementation Unit Bantan which located on Mariaman street, Teluk Papal village, Subdistrict of Bantan, Bengkalis regency. The research aims to find out the effect of feeding which is given the addition Boster Grotop with different doses in feed towards the growth and viability of seed of Red Tilapic Fish (Oreochromis sp) which keep in brackfish water. The experiment using Completely Randomized Design (CRD) of one factorial with four replication that is P0 without boster grotop (control), P1 provision of boster grotop 10 gr/kg feed, P2 provision of boster grotop 15 gr/kg feed and P3 provision of boster grotop 20 gr/kg feed. The result showed that the best boster grotop’s treatment is P3 which is give real impact on the growth and viability of Red Tilapic Fish. The best treatment is by provision of boster grotop 20 gr/kg feed. Best feed efficiency value in the treatment of 20 gr/kg feed was 97,10%keyword : boster grotop, Red Tilapic Fish (Oreochromis niloticus)